The pedunculopontine tegmental nucleus: from basic neuroscience to neurosurgical applications: Arousal from slices to humans: implications for DBS - Garcia-Rill, Edgar (2010)
One element of the reticular activating system (RAS) is the pedunculopontine nucleus (PPN), which projects to the thalamus to trigger thalamocortical rhythms and the brainstem to modulate muscle tone and locomotion. The PPN is a posterior midbrain site known to induce locomotion in decerebrate animals when activated at 40–60 Hz, and has become a target for DBS in disorders involving gait deficits. We developed a research program using brainstem slices containing the PPN to study the cellular and molecular organization of this region. We showed that PPN neurons preferentially fire at gamma band frequency (30–60 Hz) when maximally activated, accounting for the effects of electrical stimulation. In addition, we developed the P13 midlatency auditory evoked potential, which is generated by PPN outputs, in freely moving rats. This allows the study of PPN cellular and molecular mechanisms in the whole animal. We also study the P50 midlatency auditory evoked potential, which is the human equivalent of the rodent P13 potential, allowing us to study PPN-related processes detected in vitro, confirmed in the whole animal, and tested in humans. Previous findings on the P50 potential in PD suggest that PPN output in this disorder is overactive. This translational research program led to the discovery of a novel mechanism of sleep–wake control based on electrical coupling, pointing the way to a number of new clinical applications in the development of novel stimulants (e.g., modafinil) and anesthetics. In addition, it provides methods for monitoring therapeutic efficacy of DBS in humans and animal models.